MODERATE ISLAM IN LOCAL CULTURE ACCULTURATION: The Strategy of Walisongo’s Islamization - Muna, Moh. Nailul (Islamuna: Jurnal Studi Islam, 2020)
The issue of radicalism or extremism is often addressed to Muslims today. This article aims to solve the polemic of extremism because the reading of the phenomenon of extremism is done partially and refers only to conflict areas. Therefore, a series of puzzles need to be completed through religious practices in other regions. In Indonesia, many practices manifest moderate Islamic teachings. This article focuses on the process of Islamization carried out by Walisongo, especially Sunan Kudus, as an initial search for the embryo of Islamic moderation in Indonesia. Based on Emile Durkheim’s theory of social change, this article descriptively-analytically shows that the moderation of Islam in the archipelago has led to the Islamization carried out by Walisongo which was carried out in a peaceful, innovative, and inclusive way, so that the teachings of Walisongo continue to this day.[Isu radikalisme atau ekstrimisme sering dialamatkan kepada umat Islam dewasa ini Artikel ini bertujuan untuk memecahkan polemik ekstrimisme, karena pembacaan atas fenomena ekstrimisme bersifat parsial dan hanya mengarah kepada kawasan-kawasan konflik. Oleh karena itu, rangkaian puzzle perlu dilengkapi melalui praktik keagamaan di kawasan lain. Di Indonesia, banyak praktik yang memanifestasikan ajaran Islam moderat. Artikel ini fokus pada proses Islamisasi yang dilakukan Walisongo, terutama Sunan Kudus, sebagai upaya penelusuran awal terkait embrio dari moderasi Islam di Indonesia. Berdasarkan teori perubahan sosial Emile Durkheim, artikel ini secara deskriptif-analitis menunjukkan bahwa moderasi Islam di Nusantara bermuara kepada islamisasi yang dilakukan oleh Walisongo yang dilakukan dengan cara damai, inovatif, dan inklusif, sehingga ajaran Walisongo tetap lestari hingga saat ini]